Strain‐Modulated Light Emission Properties in a Single InGaN/GaN Multiple‐Quantum‐Well Microwire‐Based Flexible Light‐Emitting Diode. Issue 6 (8th April 2021) - Luo, Xingjun; Song, Weidong; Gao, Fangliang; Shi, Jiang; Cheng, Chuan; Guo, Jiaqi; He, Longfei; Liu, Qing; Yang, Yuqing; Li, Shuti; Wu, Qibao
Abstract : Micro/nanowire light‐emitting diodes (LEDs) have inspired considerable research interests due to their potential applications in microdisplays and micro/nano‐optoelectronic integrated systems. Herein, a single InGaN/GaN multiple‐quantum‐well (MQW) microwire‐based flexible LED with high‐efficiency current injection and spreading is fabricated, and the performance modulation of the device by external strain is further studied. The results show that under external compressive strains, the output power is enhanced and the peak wavelength is blue shifted; on the contrary, the output power declines and the peak wavelength is red shifted under stretch strains. Compared with strain‐free devices, the flexible LED achieves the best performance at a − 1% compressive strain, with external quantum efficiency (EQE) increasing by 14.2% and efficiency droop reducing by 17.9%. The effective improvements are attributed to external strain‐induced piezoelectric polarization charges presented at local junctions/interfaces tuning the energy band. Herein, an efficient external modulation of light emission properties in a single InGaN/GaN MQW microwire LED is presented. Abstract : It is so significant herein to fabricate an InGaN/GaN multiple‐quantum‐well microwire‐based flexible light‐emitting diode. Moreover, it further studies the modulation of performance by external strains. Surprisingly, in this experiment, modulation effects are current injection dependent, with stronger modulation capability under lower current injection. In conclusion, it lays a solid foundation for future researches on flexible devices.